问题 解答题
1
3
×(
8
3
-
5
6
)=
(13+
1
9
)×
9
13
=
66
13
×12+
66
13
=
6
5
×
2
15
+
2
15
÷
5
4
=
8
3
×(
1
3
-
8
21
×
8
16
)=
9
10
×11-
9
10
=
5
7
×
1
4
+
3
4
×
5
7
=
1
3
+
4
7
+
2
3
+
1
7
=
4
5
×
3
8
×
5
9
=
101×
1
7
-
1
7
=
6
47
×48=
1
7
×34×7×
2
17
=
答案

(1)

1
3
×(
8
3
-
5
6
),

=

1
3
×
11
6

=

11
18

(2)(13+

1
9
)×
9
13

=13×

9
13
+
1
9
×
9
13

=9+

1
13

=9

1
13

(3)

66
13
×12+
66
13

=

66
13
×(12+1),

=

66
13
×13,

=66;

(4)

6
5
×
2
15
+
2
15
÷
5
4

=

6
5
×
2
15
+
2
15
×
4
5

=(

6
5
+
4
5
)×
2
15

=2×

2
15

=

4
15

(5)

8
3
×(
1
3
-
8
21
×
8
16
),

=

8
3
×(
1
3
-
4
21
),

=

8
3
×
1
7

=

8
21

(6)

9
10
×11-
9
10

=

9
10
×(11-1),

=

9
10
×10,

=9;

(7)

5
7
×
1
4
+
3
4
×
5
7

=

5
7
×(
1
4
+
3
4
),

=

5
7
×1,

=

5
7

(8)

1
3
+
4
7
+
2
3
+
1
7

=(

1
3
+
2
3
)+(
4
7
+
1
7
),

=1+

5
7

=1

5
7

(9)

4
5
×
3
8
×
5
9

=

3
10
×
5
9

=

1
6

(10)101×

1
7
-
1
7

=(101-1)×

1
7

=100×

1
7

=

100
7

(11)

6
47
×48,

=

6
47
×(47+1),

=

6
47
×47+
6
47
×1,

=6+

6
47

=6

6
47

(12)

1
7
×34×7×
2
17

=(

1
7
×7)×(
2
17
×34),

=1×4,

=4.

单项选择题 共用题干题
单项选择题